Concepts, Mesures et Valeurs Économiques de l'éducation : Enjeux et Débats - Mahamoud Houssein (Université d'Ottawa | University of Ottawa, 2013)
In this article, we try to analyze the performance of the investment in education through lighting the theory of human capital. The current debate on the measures and values education is a major challenge for economic analysis. This analysis is part of a framework where education is playing an increasingly growing regardless of the level of economic development of countries. It is; therefore, identify the economic value of education. Despite the institutional rigidities of Djibouti, our results, using data collected by the Office of Planning in the Ministry of Education for the period (2006-2009), confirm the profitability of investment in education in three levels (primary, secondary and university.). / Dans cet article, nous tentons de faire une analyse du rendement de l’investissement éducatif à travers un éclairage de la théorie du capital humain. Le débat actuel sur les mesures et valeurs de l’éducation constitue un enjeu majeur de l’analyse économique. Cette analyse s’inscrit dans un cadre où l’enseignement prend une place de plus en plus croissante quel que soit le niveau de développement économique des pays. Il s’agit, dès lors, de cerner la valeur et la mesure économique de l’éducation. En dépit des rigidités institutionnelles de la république de Djibouti, nos résultats, à l’aide des données collectées par le bureau de la planification du ministère de l’enseignement de la période (2006-2009), mais aussi de la méthode coûts-avantages, confirment la rentabilité d’un investissement éducatif dans les différents niveaux d’enseignement (primaire, secondaire, technique et universitaire.).
Keywords: education; rate of return; cost-benefits; investment earning functions.; éducation; taux de rendement; coûts-avantages; investissement; fonctions de gains